Glycemic control and its determinants among patients with diabetes mellitus in the Teaching Hospital, Batticaloa, Sri Lanka - Kisokanth, G.; Prathapan, S.; Indrakumar, J.; Ilankoon, I. M. P. S.; Arulanandem, K. (My University, 2018)
This study aimed to identify the determinants of good glycemic control among patients with Diabetes Mellitus (DM) in Batticaloa District, Sri Lanka. A case control study was conducted among 339 patients with DM in medical clinics, Teaching Hospital, Batticaloa. Cases (n=113) were patients with DM who had fasting blood glucose equal or less than 110 mg/dl in and controls (n=226) were patients with DM who had fasting blood sugar more than 110 mg/dl in at least last 3 consecutive occasions during last 6 months. The validated and pre-tested interviewer administered questionnaire was used to collect data. Data collection was carried by the trained data collector in order to avoid interviewer bias. DM duration less than 7 years (OR 0.30, 95% CI=0.14-0.64), rural residence (OR=2.08, 95% CI=1.04-4.15), regular exercise (OR 5.96, 95% CI=3.08-11.51), fixed time for consumption of medication (OR 4.22, 95% CI=1.59-11.24), regular clinic follow-up (OR 4.61, 95% CI=1.22-17.34) and normal body weight (BMI < 23 Kg/m2) (OR 0.15, 95% CI=0.07-0.31) were found to be the factors associated with good glycemic control in the multivariate logistic regression model. Patients with DM should be advised on regular exercise, maintain the ideal body weight, regular clinic follow-up and drug compliance for the better glycemic control.
Keywords: glycemic control; diabetes mellitus; determinants; regular exercise; Sri Lanka